Tax Compliance under Indirect Rule in British Africa - Jutta Bolt; Leigh Gardner (African Economic History Network (AEHN), 2018)
How states acquire the ability to raise taxes is a central question in the study of institutions and economic development in economic history. This paper uses new data on 'ËœNative Authorities', or African local governments, to investigate tax compliance under indirect rule in British Africa. In theory, Native Authorities represented the integration of indigenous institutions into colonial rule. However, the relationships of African states with the colonial government varied, and African communities experienced considerable political and economic change during the colonial period. The paper investigates the relationship between tax compliance, the autonomy of African states within the colonial system, local levels of income and education, and Native Authority institutions. Understanding the dynamics of Native Authority tax collection helps address wider questions about African processes of state-building, the emergence of an 'uneven topography' of sub-national institutions during the colonial period, and the ways in which Africans shaped colonial rule.
Keywords: N01; N27; N37; N47; 330; Africa; tax compliance; economic history